Constructing a Computer-Aided Differential Diagnosis Engine from Open-Source APIs. - Morrison, James; Hostetter, Jason; Aggarwal, Abhi; Filice, Ross (Journal of Digital Imaging, 2016)
This paper describes the design and implementation of an application that parses and analyzes radiology report text to provide a radiologic differential diagnosis. The system was constructed using a combination of freely available web-based APIs and originally developed during the Society for Imaging Informatics in Medicine (SIIM) 2014 Hackathon. Continued development has refined and increased the accuracy of the algorithm. This project demonstrates the power and possibilities of combining existing technologies to solve unique problems as well as the stimulus of the hackathon setting to spur innovation.